Psoriasis Vulgaris in Human Immunodeficiency Virus Infected Patient: A Case Report - Rahmadewi Rahmadewi; Maya Wardiana (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2019)
Background: Psoriasis vulgaris (PV) is a chronic inflammatory skin disease characterized by erythematous thick scaly plaques. PV in human immunodeficiency virus (HIV) infected patient can give severe clinical features and challenging to treat since the treatment are immunosuppressive drugs. Purpose: To report a case of psoriasis vulgaris in HIV infected patient. Case: A 39 year-old man complained about scaly redness patches on his back and elbow that spread accompanied by burning sensation. From physical examination, on almost all over his body there were erythematous plaques sharply marginated with thick scales. Histopathologic examination from skin biopsy revealed parakeratosis, acanthosis, with psoriasiform hyperplasia and Munro’s microabscesses consistent to PV. The patient was treated with methotrexate tablets. After 8 days hospitalization, white plaque appeared on his tongue. Potassium hydroxide examination (KOH) 10% and 3 methods HIV test was done with positive result. Because of HIV positive methotrexate was stopped. Antiretroviral therapy (ART) was given and its combination with desoximetasone 0.25% cream after 10 days gave a good result for the PV. Discussion: The pathophysiology of PV in HIV infected patient seems to be conflicting due to the involvement of T cell lymphocyte in both diseases. Treatment for PV in HIV infected patient should consider the probability of the immunosuppressive effect of the drugs that can worsen the HIV infection. ART is recommended as the treatment for PV. Conclusion: Psoriatic lesion in this patient responded well to ART and desoximetasone 0.25% cream. PV in HIV infected patient requires certain management considering immunological status and immunosuppressive treatment. Early diagnosis of these comorbid condition help to determine appropriate management.